Facts and Gaps in Exercise Influence on Arrhythmogenic Cardiomyopathy: New Insights From a Meta-Analysis Approach - Martínez-Solé, Julia; Sabater-Molina, María; Braza-Boïls, Aitana; Santos-Mateo, Juan J.; Molina, Pilar; Martínez-Dolz, Luis; Gimeno, Juan R.; Zorio, Esther (Frontiers in Cardiovascular Medicine, 2021)
Arrhythmogenic cardiomyopathy (ACM) is a genetic cardiac condition characterized by fibrofatty myocardial replacement, either at the right ventricle, at the left ventricle, or with biventricular involvement. Ventricular arrhythmias and heart failure represent its main clinical features. Exercise benefits on mental and physical health are worldwide recognized. However, patients with ACM appear to be an exception. A thorough review of the literature was performed in PubMed searching for original papers with the terms “ARVC AND sports/exercise” and “sudden cardiac death AND sports/exercise.” Additional papers were then identified through other sources and incorporated to the list. All of them had to be based on animal models or clinical series. Information was structured in a regular format, although some data were not available in some papers. A total of 34 papers were selected and processed regarding sports-related sudden cardiac death, pre-clinical models of ACM and sport, and clinical series of ACM patients engaged in sports activities. Eligible papers were identified to obtain pooled data in order to build representative figures showing the global incidence of the most important causes of sudden cardiac death in sports and the global estimates of life-threatening arrhythmic events in ACM patients engaged in sports. Tables and figures illustrate their major characteristics. The scarce points of controversy were discussed in the text. Fundamental concepts were summarized in three main issues: sports may accelerate ACM phenotype with either structural and/or arrhythmic features, restriction may soften the progression, and these rules also apply to phenotype-negative mutation carriers. Additionally, remaining gaps in the current knowledge were also highlighted, namely, the applicability of those fundamental concepts to non-classical ACM phenotypes since left dominant ACM or non-plakophillin-2 genotypes were absent or very poorly represented in the available studies. Hopefully, future research endeavors will provide solid evidence about the safest exercise dose for each patient from a personalized medicine perspective, taking into account a big batch of genetic, epigenetic, and epidemiological variables, for instance, in order to assist clinicians to provide a final tailored recommendation.